Single molecule fluorescence spectroscopy - White,, JD; Fann, , WS; Sun, , WY; Su, , SC; Hsiang,, JC; Chen,, YC; Wang, , CF; Hsu, , JH (2002)
Single molecule spectroscopy can uncover fluctuation averaged out in ensemble measurements. In addition, single molecule spectroscopy naturally implies ultra-sensitive measurements, which should play important role in future proteomics and genomic research. Fluorescence method is the most commonly used single molecule detection. In this paper, we will use single conjugated polymer fluorescence spectroscopy to illustrate the power of this technique.